Microstructure, tensile properties and formability of ultrafine-grained Al–Mn square plates processed by Incremental ECAP. (November 2020) - Ciemiorek, Marta; Lewandowska, Małgorzata; Olejnik, Lech
Abstract: In the article, plates of commercial alloy 3003 were processed by Incremental Equal Channel Angular Pressing (I-ECAP). A microstructural evaluation revealed that it was possible to obtain a high fraction of high-angle grain boundaries, exceeding 63%, and an average grain size of 0.5 μm. Tensile testing revealed that the material has low ductility, but high mechanical strength, 120% higher than that of the initial material. Plate formability was described using the Lankford parameter and evaluated based on the crystallographic texture. It was concluded that the mean anisotropy was almost identical to that of the initial material, but planar anisotropy was reduced almost to 0. This was explained on the basis of the crystallographic texture. It appears that I-ECAP processed plates have qualities that could make them suitable for further processing by means of metal forming methods. Graphical abstract: Unlabelled Image Highlights: Incremental ECAP processed AA3003 plates are homogenous and isotropic and have a small grain size of 0.5 μm The dominant shear texture component leads to an r-value typical for fcc sheet metals and an uncommonly low planar anisotropy I-ECAP processed plates have qualities that could make them suitable for further processing by means of metal forming methods